Faktor Penghambat dalam Mengakses Pembiayaan pada Pengusaha Mikro di Karesidenan Madiun: Second Order CFA - Hartomi Maulana; Mohammad Zaenal Abidin (Universitas Airlangga, 2019)
This paper examines factors that may hinder micro, small and medium enterprises (MSMEs) in accessing financing from banking services in the area of Madiun Raya. Among barrier access to finance factors is complicated eligibility, low accessibilities and religious factors. However, this study further highlights three factors of barrier access to finance by using Second-order Confirmatory Factor Analysis (CFA) to validate these factors. In achieving the objectives, a quantitative approach was applied in this study. This study uses primary data collected through a questionnaire involving 146 selected respondents who have micro businesses around the Madiun Raya area which includes Magetan, Ngawi, Ponorgo, Madiun and Madiun Kota. Structural Equation Modeling (SEM) in this case, second-order CFA is used as an analysis technique. The study revealed that second order CFA validates three variables which include religious factors, low accessibility and low eligibility are in the best fit indices as factor of access barrier to finance to financial services around Madiun raya area. With the results of this study, it allows academics and researchers to find out the factors that can prevent micro businesses in accessing finance in the context of Indonesian banking institutions.